2017
DOI: 10.1155/2017/4170537
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Full Arches Supported by Tapered Implants with Knife-Edge Thread Design and Nanostructured, Calcium-Incorporated Surface: A Short-Term Prospective Clinical Study

Abstract: Purpose. To evaluate implant survival, peri-implant bone loss, and complications affecting fixed full-arch (FFA) restorations supported by implants with a knife-edge thread design and nanostructured, calcium-incorporated surface. Methods. Between January 2013 and December 2015, all patients referred for implant-supported FFA restorations were considered for enrollment in this study. All patients received implants with a knife-edge thread design and nanostructured calcium-incorporated surface (Anyridge®, Megage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
(102 reference statements)
3
16
0
Order By: Relevance
“…In accordance with Bechara et al (33) in 2017, peculiar macrotopography, characterized by knife-edge threads was capable of maximizing the primary implant stabilization in difficult situations as in the case of low-bone-quality sites.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In accordance with Bechara et al (33) in 2017, peculiar macrotopography, characterized by knife-edge threads was capable of maximizing the primary implant stabilization in difficult situations as in the case of low-bone-quality sites.…”
Section: Discussionsupporting
confidence: 79%
“…This value is known as the primary stability, which indicated a high primary stability. The high primary stability may be contributed to the knife edge threads of implant (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Although several clinical studies have shown that dental implants with a nanostructured surface enriched with calcium ions through the hydrothermal method (Xpeed ® ) can have high survival and success rates, at least in the short term [10,36,37,38,39], still little is known about the mechanism of healing these fixtures in vivo [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…However, very few clinical studies have been carried out to evaluate the implant survival rate and mechanical-technical and biological complications of restorations of this kind compared to the large number of studies on resin veneered prostheses. Thus, for fixed full-arch metal-porcelain prostheses, implant survival rates of between 95.0% and 98.7% [6,[20][21][22], have been reported for one arch or the other and for different numbers of years of loading. As in full-arch screw-retained metal-acrylic/resin prostheses, mechanical-technical complications of full-arch metal-porcelain restorations are very frequent in a range of 33.3 to 36% at ten years [6,20], although after three years of loading, 88.9% of complication-free restorations have been reported [21] Regarding biological complications, a recent study that combined full-arch metal-ceramic and metal-resin prostheses reported 73.3% of prostheses and 90% of implants as being periimplantitis-free [22].…”
Section: Introductionmentioning
confidence: 99%